2018
DOI: 10.1111/cogs.12628
|View full text |Cite
|
Sign up to set email alerts
|

Why Choo‐Choo Is Better Than Train: The Role of Register‐Specific Words in Early Vocabulary Growth

Abstract: Across languages, lexical items specific to infant‐directed speech (i.e., ‘baby‐talk words’) are characterized by a preponderance of onomatopoeia (or highly iconic words), diminutives, and reduplication. These lexical characteristics may help infants discover the referential nature of words, identify word referents, and segment fluent speech into words. If so, the amount of lexical input containing these properties should predict infants’ rate of vocabulary growth. To test this prediction, we tracked the vocab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…bang! and woof woof; see Ota et al, 2018), may thus have an influence on language development, which we explore in our regression analyses.…”
Section: Interim Discussionmentioning
confidence: 99%
“…bang! and woof woof; see Ota et al, 2018), may thus have an influence on language development, which we explore in our regression analyses.…”
Section: Interim Discussionmentioning
confidence: 99%
“…For example, clap.your.hands had a higher trigram frequency than take.your.hands, but clap and take were matched in frequency and so were clap.your and take.your. The items were constructed based on naturalistic British English infant-directed speech from the Nuffield corpus (McGillion, Pine, Herbert, & Matthews, 2017) and the Edinburgh corpus (Ota, Davies-Jenkins, & Skarabela, 2018). Combined, they yielded a dataset of 363,081 words.…”
Section: Trigram Selectionmentioning
confidence: 99%
“…One of the few studies to directly test the relation between the influence of various lexical input features on lexical development found no significant contributions from the occurrence of onomatopoeia or iconic words on subsequent lexical growth in 47 English-learning infants from 9 to 21 months (Ota et al, 2018).The study found that not iconic words, but diminutives and reduplication in the input (whether in iconic or non-iconic words) were associated with vocabulary growth. However, it should be pointed out that in many languages, the types of expressive and evaluative morphology represented by reduplication and diminutives overwhelmingly co-occur with iconic vocabulary (Mattes, 2018), suggesting it may be artificial to dissociate them.…”
Section: The Acquisition Of Iconicitymentioning
confidence: 77%